2019
DOI: 10.1111/myc.12927
|View full text |Cite
|
Sign up to set email alerts
|

Invasive aspergillosis in critically ill patients: An autopsy study

Abstract: Summary Autopsy studies show that IA is among the most commonly missed diagnoses in critically ill patients. And, because of lack of unequivocal diagnostic criteria, a timely diagnosis remains challenging. We investigate the epidemiology of and the clinical risk factors for IA in critically ill patients. We conducted a retrospective, observational study of all consecutive ICU patients with evidence of IA in the postmortem examination. During the period of the study (25 years), 893 postmortem examinations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…Recent reports indicate that invasive aspergillosis is being increasingly diagnosed in patients without above-mentioned severe neutropenia-particularly in the lung transplant recipients, patients hospitalized in the intensive care unit or treated with corticosteroids [9,11,27]. Also, individuals with chronic obstructive pulmonary disease (COPD), liver failure, and other underlying diseases are listed in this group [8,11,20]. It has been reported that in ICU patients with invasive pulmonary aspergillosis 40-80% of them do not have any malignancy or other classical risk factors for this infection [8,20].…”
Section: Clinical Forms Of Invasive Aspergillosismentioning
confidence: 99%
See 4 more Smart Citations
“…Recent reports indicate that invasive aspergillosis is being increasingly diagnosed in patients without above-mentioned severe neutropenia-particularly in the lung transplant recipients, patients hospitalized in the intensive care unit or treated with corticosteroids [9,11,27]. Also, individuals with chronic obstructive pulmonary disease (COPD), liver failure, and other underlying diseases are listed in this group [8,11,20]. It has been reported that in ICU patients with invasive pulmonary aspergillosis 40-80% of them do not have any malignancy or other classical risk factors for this infection [8,20].…”
Section: Clinical Forms Of Invasive Aspergillosismentioning
confidence: 99%
“…It has been reported that in ICU patients with invasive pulmonary aspergillosis 40-80% of them do not have any malignancy or other classical risk factors for this infection [8,20]. Moreover, in contrast to patients with neutropenia, in ICU patients the symptoms of aspergillosis are atypical; therefore the diagnosis of this infection may be delayed or omitted, according to the autopsy studies [11,15,28]. Tejerina et al showed that among 893 deceased patients, previously treated in ICU, only 40% (10 out of 25) had invasive aspergillosis diagnosed ante mortem [11].…”
Section: Clinical Forms Of Invasive Aspergillosismentioning
confidence: 99%
See 3 more Smart Citations